A strategic approach to the development of automotive dealerships in a changing market environment - D. V. Kutsyn (Путеводитель предпринимателя)
The activities of automotive dealerships need to be strategically adapted to changing market conditions. The article examines the role played by the automotive industry in the Russian economy, presents an analysis of changes in the structure of new car sales in the period from 2021 to 2023.The strategic factors that dealerships should consider when choosing a brand are described. The necessity of analyzing the competitive environment is justified, the existing marketing tactics of manufacturers are presented, the importance of the availability of spare parts and opportunities for revenue growth from after sales-service are described. The article emphasizes the need to invest in the reconstruction of dealerships, despite the inevitable financial losses, to ensure the future profitability of the business. The study provides information for players in the Russian automotive industry, helping them to change their strategy for the future development of the company in a changing market environment.